2019
DOI: 10.1111/ijcp.13306
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multivariate prediction model for nocturia, based on urinary tract etiologies

Abstract: Summary Purpose The main objective of our study was to determine which combination of modifiable and non‐modifiable parameters that could discriminate patients with nocturia from those without nocturia. This was a post‐hoc analysis of 3 prospective, observational studies conducted in Ghent University. Participants completed frequency volume chart (FVC) to compare characteristics between patients with and without nocturia. Method This was a post hoc analysis of three prospective, observational studies conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The potential of algorithms to substitute definitions for the diagnosis of nocturia has been explored in a post-hoc analysis of 3 prospective, observational studies. 21 The analysis showed that cut-off values depending on multiple factors could be replaced by statistical models that could possibly render voiding diaries redundant for many patients. The multivariate model that was used consisted of factors including voided volume, 24-hour diuresis, age, and body mass index; however, the model requires confirmation in other databases and ideally in databases that include a therapeutic arm.…”
Section: Evaluation and Classification Of Nocturia And Npmentioning
confidence: 99%
“…The potential of algorithms to substitute definitions for the diagnosis of nocturia has been explored in a post-hoc analysis of 3 prospective, observational studies. 21 The analysis showed that cut-off values depending on multiple factors could be replaced by statistical models that could possibly render voiding diaries redundant for many patients. The multivariate model that was used consisted of factors including voided volume, 24-hour diuresis, age, and body mass index; however, the model requires confirmation in other databases and ideally in databases that include a therapeutic arm.…”
Section: Evaluation and Classification Of Nocturia And Npmentioning
confidence: 99%
“…This suggests multiple causes of nocturia in co-existence, and therefore, the pathophysiology of nocturia should not be reduced to one of a handful of basic mechanisms. Because of the multifactorial etiology, we hypothesized that statistical multivariate modeling [15] may be relevant as a tool to explain clinically significant nocturia. We aimed to determine which factors were accurately associated with nocturia.…”
Section: Introductionmentioning
confidence: 99%
“…Olesen and others have made an ambitious attempt in the next article titled Development of a Multivariate Prediction Model for Nocturia, Based on Urinary Tract Etiologies . I applaud this effort and the many variables that they evaluated, but even more so I appreciate their honesty.…”
mentioning
confidence: 97%